SALARY: DOES AFFECT EMPLOYEE MOTIVATION AND PERFORMANCE? - Kusnanto Darmawan (International Journal of Accounting and Management Research, 2020)
Work is a mandatory thing that must be done to meet human needs. People work to make ends meet. One of the necessities of life can be fulfilled by means of income, namely wages or salaries. To get wages or salaries we are required to work professionally with the consequences of getting a bigger income. The purpose of this study was to determine and analyze the salary on work motivation and employee performance of UD. Sido Makmur Lumajang. population is all employees at UD. Sido Makmur Lumajang, as many as 35 employees. The sampling method used in this study was saturated samples. Methods of data analysis using Simple Linear Regression. The result of this research is that there is a relationship between salary and work motivation and employee performance.